O professor substituto: repercussões na formação inicial docente um estudo de caso - Baratto, Samuel da Silva (2010)
The origin of this case study comes from my career as a substitute in the course in Spanish letters UFSM. Investigated the representations made by graduates of this course on substitute teachers who acted with them throughout their training process, thinking about his involvement at the individual level and teacher training. The empirical field was composed of a group of five graduates who had the peculiarity in the presence graduation almost full this occupational category in the subjects who attended. The instrument for data collection was the semistructured interview. I also collected information about the course and composition of its faculty during the graduation of the study subjects. A case study, qualitative-phenomenological, in which the data have been triangulated. Based on literature review on theories of teacher education and having the background my career as a graduate student and teacher, build a sense of presence and performance of substitutes among this group of graduates. The results indicate that this category was represented as limiting devices for initial training, especially regarding the investigation. The informants represent their substitute teachers as deficient as knowledge of area and without political expression in the institution. However, regard them as pedagogically most articulate. Far from exhausting the subject, this case study is representative of what is lived by the students, without attempting to generalize or a definitive answer. In this sense, the present study is justified to bring the discussion an important aspect of higher education, which is the training of teachers serving in it, contributing to improving the training given to academic courses for undergraduate degrees.